Phthalazine based hydrazone as potent radical scavenger: Synthesis, spectral characterization, single crystal X-ray diffraction, DFT studies, molecular docking, ADME, antioxidant and antimicrobial activity of (E)-1-(2-substitutedbenzylidene)phthalazine derivatives - Surya Uthrapathy; Balasankar Thirunavukkarasu; Kodisundaram Paulrasu; Tanzeer Ahmad Dar; Manikandan Palrasu; Morris Princey; Krishnapriya Thangaretnam; Vinoth Murali (Results in Chemistry)
This study examines the synthesis, structural and biological properties of phthalazine-derived hydrazone compounds. A series of hydrazone derivatives based on phthalazine (1a-h) were synthesized. FT-IR, 1H & 13C NMR, and Mass spectrometry were used to determine their structures, while Single crystal X-ray diffraction studies identified the hydrazone tautomer. Computational studies employing density functional theory (DFT) indicated that the compounds exhibited an E-configuration about the hydrazone linkage and provided insights into the chemical reactivity and stability through FMO energies and Mulliken charge analysis. Theoretical bond parameters obtained via DFT analysis closely match the experimental data, further validating the confirmation of the synthesized compound. Molecular docking studies conducted with AutoDock 4.0, revealed docking scores from −4.87 to −7.62 kcal/mol when interacting with cytochrome C peroxidase (2X08) and E.coli reductase (1YLU) proteins highlighting potential bioactive interactions. Based on their docking scores, the synthesized compounds (1a-h) were further evaluated through In-vitro antibacterial and antioxidant assays. The results indicated that compounds with electron-donating substituents exhibit better antioxidant properties. In contrast, compounds containing electron-withdrawing groups show greater antibacterial activity. These findings suggest the potential therapeutic applications of these compounds, with distinct activities based on their electronic properties.